The Model of Moderate Islam Education - Rohana Dwi Kartikawati (The Institute of Research and Service Community IPMAFA Pati, 2022)
The research at Bahrul Maghfiroh Cinta Indonesia (BMCI) and Selamat Pagi Indonesia (SPI) High School has spesific focusses on the concept of moderate Islam; moderate Islam education; and the Implication of moderate Islam education to the student moderate behavior. This is qualitative research specified on multicase study type. Data collection is conducted by observation, interview and documentation. Data analysis is conducted by various steps, including organizing, reading and memoing, coding, interpreting, and representing the research data. The research finding shows that 1) BMCI and SPI share that moderate Islam is another term of Islam rahmatan lil ‘alamin which is practically implemented in peacefulness and flexibility. Moderate Islam values is expressed in various characters such as loving the homeland, loyalty, avoiding fanatics and the most right yourself, and tolerance, justice, mutual respect, togetherness, cooperation, responsibility, discipline, independence, honesty, seeing other perspectives, and accepting diversity. 2) Moderate Islam education implemented in BMCI is nationalist-religious educated in four steps containing briefing application, reinforcement, monitoring and evaluation. Whereas moderate Islam education implemented in SPI is nationalist-humanistic educated in three steps containing orientation, application and evaluation. 3) The implication of the students in BMCI is thought on Islam as rahmatan lil ‘alamin and comprehensive religion teaching good relationship towars human beings, animals and even plants. Moderate Islam values they learn in BMCI as moslem are politeness, friendliness, discipline, independence, tolerance, keep calm during umbragious things, sharing and discussion of diversity, being gentle, and sympathy. The students in SPI express moderate Islam values by making friends with no selection and keep holding the faith, flexible and loyal towards diversities, and seeing eagerness of worshipping form others, discipline, commitment on religious obligation, tolerance, respect, avoiding egoistic, and sharing and discussion on diversities.